(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
Pre-university high school Extension is permanently opening paths and setting academic school career. Although high school extension has its own specificities, it shares difficulties and concerns with the university extension. Curricular inclusion of ‘viable unpublished’ socio-communitarian projects in the Monserrat National High School, shows that it is possible that extension is not any longer an isolated, voluntary action, developed outside the institutional margins, but a concrete integral, critical humanistic formation integrated to the curricula, and that it articulates classroom learning with learning in the territory through experience. If we think humanism as the interculturality and universalization of human dignity, then PSC (socio-communitarian projects) are humanizing, sensing, historicizing, problematizing, articulating, democratizing, dialogical, rights promoting, curricular spaces. They also approach social problems critically as object of knowledge providing social transformation.